Application of a non-metallic catalyst in acid-base decoupling hydrogen evolution

CN117867534BActive Publication Date: 2026-10-30NINGBO RARE CARBON TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311693597.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-11
Publication Date
2026-10-30
Estimated Expiration
2043-12-11

AI Technical Summary

Technical Problem

该方法中需要采用王水等强酸,故环境友好性较差

Benefits of technology

[0040](1)杂原子掺杂是提升碳材料催化性能常用的修饰方法,其中,氮掺杂经过大量实验和理论模拟被证实是最有效的掺杂方法,本发明以NH3和PDDA或含氮杂环化合物(例如吡咯、N-甲基吡咯、吡唑或N-甲基吡唑等)为N源,本发明采用的氮源含N丰富、价格低廉、具有吸电子能力,将其作为氮源制备N掺杂碳材料(N@C),利用碳基材料自身作为催化剂活性相,通过掺N来激活碳基材料本身的催化活性,研磨使得碳材料混合物复合充分,电解水制氢阳极片状N@C碳基非金属催化剂的方法制备条件温和,工艺操作简单,对设备要求低,重复性良好,制备得到的N掺杂N@C片状碳基非金属催化剂比表面积大、活性组分多、结构可调、具有高反应动力学、OER性能优异,化学稳定性良好,在NH3保护气氛下退火完成的N@C片状碳基非金属催化剂材料,在酸碱解耦电解制氢领域具有广阔的应用前景,可以推动其发展。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117867534B_ABST
    Figure CN117867534B_ABST
Patent Text Reader

Abstract

The application discloses application of a nonmetallic catalyst in acid-base decoupling hydrogen evolution, and belongs to the technical field of hydrogen production by water electrolysis. A preparation method of the nonmetallic catalyst comprises the following steps: taking carbon nanotubes, conductive carbon black, graphite and activated carbon as raw materials, adding phenolic resin and a nitrogen source, uniformly mixing, cold-pressing and forming to obtain a green compact, cold-pressing and forming by using a tablet press to obtain a sheet-shaped nonmetallic catalyst, and high-temperature heat treatment of the green compact in an ammonia atmosphere to prepare a sheet-shaped N@C nonmetallic catalyst. The N@C carbon-based nonmetallic electrode has a cost of 1 / 2500 of a commercial noble metal catalyst iridium oxide, has more exposed active components, superior OER performance and high reaction kinetics, and the acid-base mixed solution decoupling electrolysis hydrogen production has superior performance compared with single electrolyte acid or alkali solution electrolysis hydrogen production. The preparation method of the N@C carbon-based nonmetallic electrode has mild conditions and simple process operation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of water electrolysis for hydrogen production, specifically relating to the application of a non-metallic catalyst in acid-base decoupling hydrogen production. Background Technology

[0002] Hydrogen energy is an abundant, green, low-carbon, and widely used secondary energy source. Hydrogen is produced by electrolyzing water using renewable energy sources such as wind power. This process produces virtually no greenhouse gases, hence the term "zero-carbon hydrogen." However, the oxygen evolution reaction (OER) in water electrolysis is a multi-electron process, which suffers from short stability, high overpotential, and low energy efficiency. Currently, the main anode catalyst for commercial KOH solution electrolysis to produce hydrogen is Raney nickel. Compared to commercially available precious metal catalysts like IrO2 and RuO2 for PEM electrolysis of pure water, Raney nickel exhibits lower catalytic activity under the same reaction conditions when used as the anode.

[0003] Carbon materials are materials composed of carbon elements without constant structure and properties. Doping carbon materials with nitrogen as a heteroatomum to prepare non-metallic electrode sheets can theoretically improve the conductivity of carbon materials, alter the electronic configuration and atomic structure of carbon atoms and surrounding atoms, and greatly enhance the electrocatalytic hydrogen production performance. Acid-base decoupled electrolytic hydrogen production, by coupling the hydrogen evolution reaction in an acidic environment with the oxidation reaction in an alkaline environment to construct an amphoteric hybrid electrolytic hydrogen production cell, can overcome the bottleneck problem of dependence on precious metal catalysts in current water electrolysis hydrogen production processes.

[0004] For example, patent application CN110117797A discloses an electrolytic cell and its application in hydrogen production by water electrolysis. In this method, the anode catalyst and the cathode catalyst used for acid-base decoupling electrocatalytic hydrogen production are both Ru-RuO2 / CNT composite catalysts, which are composites of precious metals and carbon materials. However, precious metals are expensive, and the raw materials are imported resources, which are easily monopolized by the market. Secondly, the HER performance diagram and OER performance diagram in this method cannot intuitively show the amount of hydrogen and oxygen produced and the purity of the produced gas.

[0005] For example, patent application CN113430537A discloses a method for preparing an oxygen evolution electrocatalyst using an N-doped carbon-based material. The preparation process of this catalyst requires freeze-drying for 3 hours to freeze the water-containing material below the freezing point. Therefore, this method requires the ice to be converted into vapor and removed under strict vacuum conditions.

[0006] For example, patent application CN113089136A discloses a platinum-supported nitrogen / sulfur co-doped porous carbon nanofiber material and its preparation and application in the fields of fuel cells and water electrolysis for hydrogen production. The carbonization process temperature of this material is 600-1000℃, and the holding time is 2-5h. The preparation process of this catalyst requires loading platinum precious metal onto porous carbon nanofibers, and the holding time is long, resulting in high energy consumption.

[0007] For example, patent application CN111001428A discloses a metal-free carbon-based electrocatalyst, its preparation method, and its application. This catalyst can be used in electrochemical hydrogen evolution reaction, oxygen evolution reaction, and oxygen reduction reaction. However, the catalyst preparation process requires soaking the resulting black product in aqua regia for 6 hours, then washing it until neutral, and finally soaking it in concentrated nitric acid at 70°C for 12 hours. This method requires the use of strong acids such as aqua regia, thus exhibiting poor environmental friendliness. Summary of the Invention

[0008] To address the aforementioned technical problems, this invention provides the application of an N@C nonmetallic catalyst in the electrolysis of water to produce hydrogen and / or oxygen. Preferably, it is used in acid-base decoupled electrolysis for hydrogen and / or oxygen production. For example, its application as an anode in the electrolysis of water to produce hydrogen and / or oxygen. Exemplarily, it is used as an anode in acid-base decoupled electrolysis for hydrogen and / or oxygen production.

[0009] Specifically, the present invention provides the following technical solution:

[0010] The application of a catalyst in acid-base decoupled electrolytic hydrogen production and / or oxygen production, said catalyst being prepared by a method comprising the following steps:

[0011] The catalyst is prepared by mixing a carbon source with phenolic resin and a nitrogen source, pressing it into a compact, and then heat-treating it at high temperature in an ammonia atmosphere.

[0012] According to an embodiment of the present invention, the nitrogen source is selected from at least one of polydiallyldimethylammonium chloride (PDDA) or nitrogen-containing heterocyclic compounds (e.g., pyrrole, N-methylpyrrole, pyrazole or N-methylpyrazole, etc.), preferably polydiallyldimethylammonium chloride (PDDA).

[0013] According to embodiments of the present invention, the carbon source is selected from one, two, or more of carbon nanotubes, conductive carbon black, graphite, and activated carbon, preferably from a mixture of carbon nanotubes, conductive carbon black, graphite, and activated carbon. For example, the mass ratio of the carbon nanotubes, conductive carbon black, graphite, and activated carbon is 2–8:2–8:1–8:0.5–7, with exemplary ratios of 5:5:1:2.5, 5:5:2:1.5, 5:5:3:0.5, 5:5:2.5:1, 7:7:7:6, and 8:8:6:5.

[0014] According to an embodiment of the present invention, the amount of phenolic resin used is 10% to 30% of the total mass of the carbon source, and exemplary amounts are 10%, 11%, 12%, 13%, 14%, 15%, 20%, 22%, 24%, 25%, 26%, 28%, and 30%.

[0015] According to an embodiment of the present invention, the amount of nitrogen source used is 20% to 40% of the total mass of carbon source, and exemplary amounts are 20%, 21%, 22%, 23%, 24%, 25%, 30%, 32%, 34%, 35%, 36%, 38%, and 40%.

[0016] According to an embodiment of the present invention, the mixing method is, for example, grinding. For example, the grinding time is 10 to 60 minutes, exemplarily 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, and 60 minutes.

[0017] According to an embodiment of the present invention, the compression molding method is cold pressing. For example, the compression molding pressure is 10-30 MPa, exemplarily 20 MPa; the compression molding holding time is 1-5 min, exemplarily 1 min, 2 min, 3 min, 4 min, and 5 min.

[0018] According to an embodiment of the present invention, the diameter of the molded blank can be 10-15 mm, exemplarily 13 mm; the thickness of the molded blank is 1-3 mm, exemplarily 2 mm.

[0019] According to an embodiment of the present invention, the molded blank is sheet-shaped with a uniform surface texture and a silvery luster.

[0020] According to an embodiment of the present invention, the high-temperature heat treatment involves, for example, placing the cold-pressed compact in a vacuum-sealed ammonia atmosphere for high-temperature heat treatment. For example, the NH3 gas flow rate is 50–150 ml / min, exemplarily 50 ml / min, 80 ml / min, 100 ml / min, 120 ml / min, or 150 ml / min.

[0021] According to an embodiment of the present invention, the temperature of the high-temperature heat treatment is 800-1000℃, exemplarily 800℃, 900℃, or 1000℃; the isothermal time of the high-temperature heat treatment is 100-150 min, exemplarily 100 min, 110 min, 120 min, 130 min, 140 min, or 150 min; and the heating rate of the high-temperature heat treatment is 5-8℃ / min, exemplarily 5℃ / min, 6℃ / min, 7℃ / min, or 8℃ / min.

[0022] According to an exemplary embodiment of the present invention, the high-temperature heat treatment method is as follows: under normal pressure conditions, starting from room temperature, the temperature is increased at a rate of 5-8°C / min, and after 150-200min, the temperature is increased to 800-1000°C, then held at a constant temperature for 100-150min, and then naturally cooled to room temperature in the furnace to obtain the catalyst.

[0023] According to an embodiment of the present invention, the catalyst is an N-doped carbon-based nonmetallic catalyst, denoted as N@C.

[0024] According to an embodiment of the present invention, the catalyst is in the form of a sheet. For example, the diameter of the catalyst can be 10-15 mm, exemplarily 13 mm; the thickness of the catalyst is 1-3 mm, exemplarily 2 mm.

[0025] According to an embodiment of the present invention, the amount of N doped in the catalyst is 1 to 5%, preferably 1.80% to 2.00%, and exemplary amounts are 1%, 1.85%, 1.89%, 1.92%, 2%, 3%, 4%, and 5%.

[0026] According to an embodiment of the present invention, the catalyst has an average specific surface area of ​​190–200 m². 2 / g, for example 195.025m 2 / g.

[0027] According to an embodiment of the present invention, in the acid-base decoupled electrolysis for hydrogen and / or oxygen production, the catalyst is directly used as the anode electrode.

[0028] According to an embodiment of the present invention, the electrolyte used in the anode is an alkaline solution, such as a KOH solution. For example, the concentration of the electrolyte used in the anode is 0.50 to 1.00 M, with exemplary concentrations of 0.50 M, 0.75 M, and 1.00 M.

[0029] According to an embodiment of the present invention, the electrolyte used in the cathode for producing hydrogen and / or oxygen by electrolysis of water is an acidic solution, such as an H2SO4 solution. For example, the concentration of the electrolyte used in the cathode is 0.50 to 1.00 M, with 0.50 M, 0.75 M, and 1.00 M being exemplary.

[0030] According to an embodiment of the present invention, the driving potential for the electrolysis of water to produce hydrogen and / or oxygen is not less than 0.401V.

[0031] According to an embodiment of the present invention, the cathode for the electrolysis of water to produce hydrogen and / or oxygen is, for example, a platinum sheet.

[0032] The present invention also provides an electrolysis system comprising an anode electrode sheet, wherein the anode electrode sheet is a catalyst prepared in the above-described applications.

[0033] According to an embodiment of the present invention, the electrolysis system further includes a cathode electrode plate, a bipolar membrane, an anode electrolyte and a cathode electrolyte, wherein the anode electrolyte and the cathode electrolyte are separated by the bipolar membrane.

[0034] According to an embodiment of the present invention, the cathode electrode sheet is, for example, a platinum sheet.

[0035] According to an embodiment of the present invention, the electrolyte in the anode chamber is an alkaline solution, such as a KOH solution. For example, the concentration of the electrolyte used in the anode chamber is 0.50 to 1.00 M, with exemplary concentrations of 0.50 M, 0.75 M, and 1.00 M.

[0036] According to an embodiment of the present invention, the cathode chamber electrolyte is an acidic solution, such as an H2SO4 solution. For example, the concentration of the cathode chamber electrolyte is 0.50 to 1.00 M, with exemplary concentrations being 0.50 M, 0.75 M, and 1.00 M.

[0037] According to an embodiment of the present invention, the bipolar membrane is, for example, a Nafion 117 membrane.

[0038] The present invention also provides the application of the above-described electrolysis system in the electrolysis of water to produce hydrogen and / or oxygen. Preferably, it is used in the decoupled electrolysis of acid and base to produce hydrogen and / or oxygen.

[0039] The beneficial effects of this invention are:

[0040] (1) Heteroatom doping is a commonly used modification method to improve the catalytic performance of carbon materials. Among them, nitrogen doping has been proven to be the most effective doping method through a large number of experiments and theoretical simulations. In this invention, NH3 and PDDA or nitrogen-containing heterocyclic compounds (such as pyrrole, N-methylpyrrole, pyrazole or N-methylpyrazole, etc.) are used as nitrogen sources. The nitrogen sources used in this invention are rich in nitrogen, inexpensive, and have electron-withdrawing ability. They are used as nitrogen sources to prepare N-doped carbon materials (N@C). The carbon-based materials themselves are used as the active phase of the catalyst. The catalytic activity of the carbon-based materials is activated by doping with N. Grinding ensures thorough composite formation of the carbon material mixture. The method for preparing the N@C carbon-based nonmetallic catalyst for hydrogen production via water electrolysis is characterized by mild preparation conditions, simple operation, low equipment requirements, and good reproducibility. The prepared N-doped N@C carbon-based nonmetallic catalyst exhibits a large specific surface area, multiple active components, tunable structure, high reaction kinetics, excellent OER performance, and good chemical stability. The N@C carbon-based nonmetallic catalyst material annealed under an NH3 protective atmosphere has broad application prospects in the field of acid-base decoupled electrolysis for hydrogen production and can promote its development.

[0041] (2) This invention, through a reasonable high-temperature heat treatment process, obtained a sheet-like non-metallic electrode sheet for the electrocatalytic oxygen evolution reaction with suitable pore structure, thickness, and nitrogen doping content. Using a Hoffman electrolysis water circulation device with different acid-base mixed concentration gradients as the electrolyte, the prepared N@C sheet-like carbon-based non-metallic catalyst was used as the anode, and a platinum sheet as the cathode. In an acid-base decoupled electrocatalytic hydrogen production environment of 0.50M H2SO4 / 1.00M KOH, the hydrogen yield reached 14.1 ml / h, which is superior to the 12.5 ml / h hydrogen yield of the same specification N@C sheet-like carbon-based non-metallic catalyst as the anode and platinum sheet as the cathode in the same acid-base decoupled electrocatalytic hydrogen production environment of 0.50M H2SO4 / 0.75M KOH. This is also superior to the 14.1 ml / h hydrogen yield of the same specification N@C sheet-like carbon-based non-metallic catalyst as the anode and platinum sheet as the cathode in the same acid-base decoupled electrocatalytic hydrogen production environment of 0.50M H2SO4 / 0.75M KOH. The hydrogen yield in the acid-base decoupled electrocatalytic hydrogen production environment using KOH is 8.5 ml / h, which is superior to the 13.2 ml / h hydrogen yield of the equivalent commercial electrode using IrO2 as the anode and platinum as the cathode in the 0.5 M H2SO4 / 1 M KOH acid-base decoupled electrocatalytic hydrogen production environment; it is also superior to the 10.5 ml / h hydrogen yield of the equivalent commercial electrode using IrO2 as the anode and platinum as the cathode in the 0.50 M H2SO4 / 0.75 M KOH acid-base decoupled electrocatalytic hydrogen production environment; and it is superior to the 8.2 ml / h hydrogen yield of the equivalent commercial electrode using IrO2 as the anode and platinum as the cathode in the 0.50 M H2SO4 / 0.50 M KOH acid-base decoupled electrocatalytic hydrogen production environment. The N@C nonmetallic electrode exhibits excellent OER performance, and the OER reaction promotes the HER reaction, increases the rate of hydrogen electrolysis, and accelerates the reaction kinetics.

[0042] (3) The acid-base mixed decoupled electrocatalytic hydrogen production method adopted in this invention has excellent hydrogen production performance compared with single electrolyte acid or alkali solutions by selecting a suitable acid-base mixed concentration gradient. Theoretically, the acid-base mixed decoupled electrolyzer can achieve complete water separation at an applied voltage as low as 0.401V, realizing the effective utilization of electrochemical neutralization energy. Its acid-base mixed decoupled electrocatalytic hydrogen evolution performance is excellent, and the Hoffman diagram clearly and intuitively quantifies the volume of hydrogen and oxygen produced.

[0043] (4) The catalyst of the present invention does not use harsh operating techniques such as freeze drying in its preparation process. The process is simple and easy to industrialize.

[0044] (5) In the process of preparing N@C sheet-like carbon-based non-metallic catalyst materials, this invention does not use highly toxic chemicals, precious metals or non-precious metals, but uses non-metals as raw materials to avoid the waste of metals and the raw material cost is low.

[0045] (5) This invention does not use a large amount of aqua regia or other strong acidic solutions to treat the catalyst, thus having sustainable development and environmental friendliness. Attached Figure Description

[0046] Figure 1 This is a diagram of a tube furnace high-temperature heat treatment apparatus for the N@C sheet-like non-metallic catalysts prepared in Examples 1, 2, and 3.

[0047] Figure 2 a is an optical image and a scanning electron microscope image of the N@C sheet-like non-metallic catalysts prepared in Examples 1, 2, and 3. Figure 2 b is an optical image and a scanning electron microscope image of the N@C sheet-like non-metallic catalyst prepared in Example 4.

[0048] Figure 3 This is a sample adsorption-desorption and cumulative pore volume performance diagram of the N@C sheet-like carbon-based non-metallic catalyst prepared in Example 1.

[0049] Figure 4 In the image, a, b, and c are the XPS full spectra of the N@C sheet-like carbon-based nonmetallic catalysts prepared in Examples 1, 2, and 3, respectively.

[0050] Figure 5 In the image, a, b, and c are the XRD patterns of the N@C sheet-like carbon-based nonmetallic catalysts prepared in Examples 1, 2, and 3, respectively.

[0051] Figure 6 The graph shows the hydrogen and oxygen production rates plotted using a commercial electrode with IrO2 as the anode and Pt as the cathode, after three tests at nine acid-base mixed concentration gradients, with the average value taken.

[0052] Figure 7 The graph shows the hydrogen and oxygen production rates plotted using N@C sheet-like carbon-based non-metallic carbon electrodes prepared in Examples 1, 2, and 3 as anodes and Pt sheets as cathodes, with the electrodes tested three times under nine acid-base mixed concentration gradients and the average value taken.

[0053] Figure 8 This is a diagram of the reaction apparatus for acid-base mixed decoupled electrocatalytic hydrogen evolution of the present invention. The left side is the anode, with KOH as the electrolyte, and the right side is the cathode, with H₂SO₄ as the electrolyte. A Nafion 117 membrane separates the anode and cathode chambers (to prevent neutralization reactions from occurring and reducing the concentration gradient, thus preventing the utilization of neutralization energy). Detailed Implementation

[0054] The technical solution of the present invention will be further described in detail below with reference to specific embodiments. It should be understood that the following embodiments are merely illustrative and explanatory of the present invention, and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are covered within the scope of protection intended by the present invention.

[0055] Unless otherwise stated, the raw materials and reagents used in the following examples are commercially available products or can be prepared by known methods.

[0056] In the following examples of the present invention, the concentrated sulfuric acid used has a mass fraction of 98%, and the KOH has a purity GR of 85%.

[0057] Example 1

[0058] Accurately weigh carbon nanotubes (purchased from Inokai Reagent Network, purity: ≥95%, diameter: 20-40nm, length: 1-2μm) and conductive carbon black (purchased from Inokai Reagent Network, average primary particle size: 30-45nm, specific surface area: ~125m²) using a 0.1 g balance. 2 / g, Loose bulk density: ~0.273g / cm³ 3 Compacted density: ~0.4 g / cm³ 3 Relative tinting strength: ~105%, volatile matter (950℃): ~1.5%, DBP absorption: ~150mg / 100g, pH: ~8), graphite (Innokai Reagent Network, CASNO: 7782-42-5, molecular weight: 12.01, purity: 99.95%), activated carbon (purchased from Innokai Reagent Network, particle size: 5±1μm, specific surface area: 1800±100m²). 2 / g), pore volume: 1.0~1.2cm 3 The carbon material powder (containing 1000 mg, 1000 mg, 200 mg, and 500 mg of a mixture with the following properties: pore size: 2.0-2.2 nm, carbon content: >95%, density: 0.38-0.40 g / cc, pH: 6.5-7.5) in a mass ratio of 5:5:1:2.5, was placed in an agate mortar. 0.50 ml of phenolic resin (purchased from Inokai Reagent Network, CasNo: 9003-35-4) and 1.00 ml of polydiallyldimethylammonium chloride (PDDA, purchased from Inokai Reagent Network, CasNo: 26062-79-3, molecular formula: C8H) were added. 16 ClN) n The mixture (containing 8.6% nitrogen) was thoroughly ground for 30 minutes to ensure uniform mixing. 1 / 9 of the mixed raw material powder (300 mg) was randomly weighed from the 2700 mg formulation and placed in a tablet press for cold pressing at 20 MPa for 1 minute. After depressurization, a compact was obtained. The compact had a diameter of 13 mm, a thickness of 2 mm, and a uniform surface texture with a silvery luster. Figure 1 The pressed preform was placed in a vacuum atmosphere of ammonia for high-temperature heat treatment. The flow rate of NH3 gas was 100 ml / min. The high-temperature heat treatment procedure was as follows: under normal pressure, the temperature was increased from room temperature to 900℃ at a rate of 5℃ / min for 180 min, then held at the temperature for 120 min, and then naturally cooled to room temperature with the furnace to obtain a uniform black N@C sheet-like carbon-based non-metallic catalyst.

[0059] Example 2:

[0060] Accurately weigh 1000 mg, 1000 mg, 400 mg, and 300 mg of carbon nanotubes, conductive carbon black, graphite, and activated carbon (specifications as in Example 1) into a 0.1% balance, with a mass ratio of 5:5:2:1.5. Place the carbon material powder in an agate mortar, add 0.50 ml of phenolic resin and 1.00 ml of PDDA (specifications as in Example 1), and grind thoroughly for 30 minutes to mix evenly. Randomly weigh 1 / 9 of the mixed raw material powder (300 mg) from the 2700 mg raw material ratio, place it in a tablet press for cold pressing at a pressure of 20 MPa for 1 minute, and release the pressure to obtain a sheet-like carbon-based non-metallic catalyst. The compact has a diameter of 13 mm, a thickness of 2 mm, and a uniform surface texture with a silvery luster. Place the compact in a vacuum atmosphere of ammonia for high-temperature heat treatment at a flow rate of 100 ml / min. The high-temperature heat treatment procedure was as follows: under normal pressure, starting from room temperature, the temperature was increased at a rate of 5°C / min, reaching 900°C after 180 min, then held at that temperature for 120 min, and finally allowed to cool naturally to room temperature in the furnace. This yielded a uniformly structured black N@C sheet-like carbon-based nonmetallic catalyst. The testing method was the same as in Example 1, and the structural characterization results are as follows: Figure 4 b, Figure 5 As shown in b.

[0061] Example 3:

[0062] Accurately weigh 1000 mg, 1000 mg, 600 mg, and 100 mg of carbon nanotubes, conductive carbon black, graphite, and activated carbon (specifications as in Example 1) into a balance with a mass ratio of 5:5:3:0.5. Place the carbon material powder in an agate mortar, add 0.50 ml of phenolic resin and 1.00 ml of PDDA (specifications as in Example 1), and grind thoroughly for 30 minutes to mix evenly. Randomly weigh 1 / 9 of the mixed carbon material powder (300 mg) from the 2700 mg raw material mixture, place it in a tablet press for cold pressing at a pressure of 20 MPa for 1 minute, and release the pressure to obtain a sheet-like carbon-based non-metallic catalyst. The compact has a diameter of 13 mm, a thickness of 2 mm, and a uniform surface texture with a silvery luster. Place the compact in a vacuum atmosphere of ammonia for high-temperature heat treatment at a flow rate of 100 ml / min. The high-temperature heat treatment procedure was as follows: under normal pressure, starting from room temperature, the temperature was increased at a rate of 5°C / min, reaching 900°C after 180 min, then held at that temperature for 120 min, and finally allowed to cool naturally to room temperature in the furnace. This yielded a uniformly structured black N@C sheet-like carbon-based nonmetallic catalyst. The testing method was the same as in Example 1, and the structural characterization results are as follows: Figure 4 c, Figure 5 As shown in c.

[0063] Example 4

[0064] Accurately weigh 1000 mg, 1000 mg, 200 mg, and 500 mg of carbon nanotubes, conductive carbon black, graphite, and activated carbon (specifications as in Example 1) into a 0.1% balance, with a mass ratio of 5:5:1:2.5. Place the carbon material powder in an agate mortar, add 0.20 ml of phenolic resin and 0.5 ml of PDDA (specifications as in Example 1), and grind thoroughly for 30 minutes to mix evenly. Randomly weigh 1 / 9 of the mixed carbon material powder (300 mg) from the 2700 mg raw material mixture, place it in a tablet press for cold pressing at a pressure of 20 MPa for 1 minute, and release the pressure to obtain a sheet-like carbon-based non-metallic catalyst. The compact has a diameter of 13 mm, a thickness of 2 mm, and a uniform surface texture with a silvery luster. Place the compact in a vacuum atmosphere of ammonia for high-temperature heat treatment at a flow rate of 100 ml / min. The high-temperature heat treatment procedure was as follows: under normal pressure, the temperature was increased from room temperature to 900℃ at a rate of 5℃ / min for 180 min, then held at that temperature for 120 min, and then naturally cooled to room temperature with the furnace to obtain a uniform black N@C sheet-like carbon-based non-metallic catalyst. The test method was the same as in Example 1.

[0065] Figure 2Image a shows the optical image and scanning electron microscope (SEM) image of the N@C sheet-like non-metallic catalysts prepared in Examples 1, 2, and 3. The optical image shows that the surface of the prepared N@C sheet-like carbon-based non-metallic catalyst has a uniform silvery luster. The SEM image shows that the N@C sheet-like carbon-based non-metallic catalyst powder is uniform and has a graphite sheet nanostructure. The sheet-like structure can provide a larger specific surface area, thereby improving the electrocatalytic activity of the electrocatalyst. Figure 2 Figure b shows the optical image and scanning electron microscope (SEM) image of the N@C sheet-like non-metallic catalyst prepared in Example 4. As can be seen from the figure, changing the amount of phenolic resin and nitrogen source results in excessively low mechanical strength of the prepared non-metallic electrode sheet. This leads to a short stability time when used as a clip-on electrode for acid-base decoupling electrolytic hydrogen evolution testing. Furthermore, the SEM scan shows that the catalyst particles are small and lack graphite sheet nanostructures.

[0066] Figure 3 The adsorption-desorption and cumulative pore volume curves of the N@C sheet-like carbon-based non-metallic catalysts prepared in Examples 1, 2, and 3 are calculated by averaging the values ​​from the three examples. The specific surface area is generally analyzed using the BET (Brunauer-Emmett-Teller) method. The specific surface area of ​​the N@C non-metallic catalyst is determined to be 189.593 m² / s² from the gas adsorption curves. 2 / g, the pore size distribution is usually modeled using the BJH (Barrett-Joiner-Halenda) model, with an average pore size of 5.7 nm. This isotherm belongs to Type IV in the IUPAC classification, with H1 hysteresis loop. As can be seen from the figure, the adsorption amount increases gradually in the low-pressure range. At this point, N2 molecules are adsorbed in monolayers to multilayers on the inner surface of the mesopores. When calculating the specific surface area using the BET method for ordered mesoporous materials, a relative pressure p / p0 = 0.10–0.30 is suitable. There is a sudden increase in adsorption amount around p / p0 = 0.8–1.0. The position of this range reflects the size of the sample pores, and the width of its variation can be used as a basis for measuring the uniformity of the mesopores.

[0067] Figure 4 In Figures a, b, and c, the XPS full spectra of the N@C sheet-like carbon-based non-metallic catalysts prepared in Examples 1, 2, and 3 are shown respectively. The figures indicate that the N@C sheet-like carbon-based non-metallic catalysts are composed of C, N, and O elements, demonstrating that N element was successfully incorporated into the carbon material. XPS analysis revealed that the atomic percentages of N element doping in the N@C sheet-like carbon-based non-metallic catalysts prepared in Examples 1, 2, and 3 were 1.85%, 1.89%, and 1.92%, respectively, with the nitrogen element atomic percentage ranging from 1.80% to 2.00%.

[0068] Figure 5In the figures, a, b, and c are the XRD patterns of the N@C sheet-like carbon-based nonmetallic catalysts prepared in Examples 1, 2, and 3, respectively. The XRD patterns show that the N@C sheet-like carbon-based nonmetallic catalysts prepared in Examples 1, 2, and 3 are mainly composed of the Graphite-2H phase, which is stacked in a thermodynamically stable ABAB (hexagonal, 2H) configuration. The three examples match the standard card PDF#41-1487, indicating that the materials have high strength.

[0069] Figure 6 The commercial electrode consists of IrO2 as the anode and Pt as the cathode, with a single electrode area of ​​1 cm². 2 The electrode was tested three times at nine concentration gradients, and the average value was used as the plotting standard for single acid-base mixture decoupling hydrogen evolution. The hydrogen and oxygen production rate of electrocatalytic hydrogen evolution under the applied voltage of 2V was obtained. Each sample was tested three times and the average value was obtained to reduce experimental error and make statistical graphs. Using a commercially available IrO2 electrode of equivalent specifications as the anode and a platinum sheet as the cathode, the hydrogen yield was 8.2 ml / h in an acid-base decoupled electrocatalytic hydrogen evolution environment of 0.50 M H2SO4 / 0.50 M KOH. Using the same commercially available IrO2 electrode of equivalent specifications as the anode and a platinum sheet as the cathode, the hydrogen yield was 10.5 ml / h in an acid-base decoupled electrocatalytic hydrogen evolution environment of 0.50 M H2SO4 / 0.75 M KOH. Using the same commercially available IrO2 electrode of equivalent specifications as the anode and a platinum sheet as the cathode, the hydrogen yield was 13.2 ml / h in an acid-base decoupled electrocatalytic hydrogen evolution environment of 0.50 M H2SO4 / 1.00 M KOH (the linear fitting equation was y = 13.2 * x, with an error of ±0.1 ml, where y is the hydrogen production in ml and x is the time in h). The hydrogen and oxygen production rates of 0.75M sulfuric acid solution and 1.00M sulfuric acid solution as the cathode electrolyte for acid-base decoupling electrolytic hydrogen production can be obtained similarly to those of KOH solutions of different concentrations. Considering the cost of concentrated sulfuric acid and KOH, a concentration gradient of 0.50M H2SO4 / 1.00M KOH is preferred for acid-base mixed decoupling electrolytic hydrogen production. A comparative experiment was conducted under the same conditions using the N@C non-metallic electrode prepared in this patent as the anode and a platinum sheet as the cathode.

[0070] The pH values ​​of the sulfuric acid solution and the potassium hydroxide solution are shown in the table below:

[0071]

[0072] The basic parameters of the Hoffmann electrochemical hydrogen analyzer are as follows:

[0073]

[0074] The concentration gradient combinations for decoupled electrolytic hydrogen generation using commercial electrodes (anode: IrO2, cathode: Pt) are shown in the table below:

[0075]

[0076] Figure 7 The anode is an N@C sheet-like carbon-based non-metallic catalyst used directly as the electrode, and the cathode is a Pt sheet with a single electrode area of ​​1 cm². 2The N@C sheet-like carbon-based non-metallic catalysts from Examples 1, 2, and 3 were directly used as anodes and tested three times at each of the nine concentration gradients. The average value of the measured values ​​from Examples 1, 2, and 3 was used as the plotting standard for hydrogen evolution by acid-base mixture decoupling at a single concentration. This yielded a graph of hydrogen and oxygen production rates for electrocatalytic hydrogen evolution at different concentrations under an applied voltage of 2V (wherein: the N@C sheet-like carbon-based non-metallic catalysts in each example were directly used as electrodes and tested three times to obtain the average value to reduce experimental error). The results showed that the average hydrogen yield of the N@C sheet-like carbon-based non-metallic catalysts used in Examples 1, 2, and 3, with platinum sheets as cathodes and directly as anodes, was 8.5 ml / h in an acid-base decoupled electrocatalytic hydrogen evolution environment of 0.50 M H2SO4 / 0.50 M KOH. The average hydrogen yield of the N@C sheet-like carbon-based non-metallic catalysts used in Examples 1, 2, and 3, with platinum sheets as cathodes, was 12.5 ml / h in an acid-base decoupled electrocatalytic hydrogen evolution environment of 0.50 M H2SO4 / 0.75 M KOH. The average hydrogen yield of the N@C sheet-like carbon-based non-metallic catalysts used in Examples 1, 2, and 3, with platinum sheets as cathodes, was 14.1 ml / h in an acid-base decoupled electrocatalytic hydrogen evolution environment of 0.50 M H2SO4 / 1.00 M KOH (the linear fitting equation was y = 14.1 * x, with an error of ±0.1 ml, where y is the hydrogen production in ml and x is the time in h). In acid-base decoupled electrolytic hydrogen evolution, using 0.75M and 1.00M sulfuric acid solutions as the cathode electrolyte and KOH solutions of different concentrations as the anolyte, the hydrogen and oxygen production rates can be obtained similarly. Considering the cost of concentrated sulfuric acid and KOH, an N@C sheet-like carbon-based non-metallic catalyst is preferred as the anode, and a Pt sheet as the cathode. The hydrogen and oxygen production rates in a 0.50M H₂SO₄ / 1.00M KOH acid-base mixed decoupled electrolytic hydrogen evolution are comparable to those of a commercial electrode with IrO₂ as the anode and a Pt sheet as the cathode in a 0.50M H₂SO₄ / 1.00M KOH solution. A comparison of hydrogen and oxygen production rates in the decoupled electrolytic hydrogen production using KOH acid-base mixtures reveals that: The N@C sheet-like carbon-based non-metallic catalyst of this invention, used directly as the anode, achieves a hydrogen production rate of 14.1 ml / h at the cathode, which is higher than the 13.2 ml / h produced by using commercial IrO2 as the anode and Pt cathode under the same reaction conditions. The hydrogen production rate is directly proportional to time, and the low oxygen production improves the safety factor. This indicates that the N@C sheet-like carbon-based non-metallic catalyst of this invention exhibits good thermodynamic activity, fast kinetic rate, and high hydrogen production rate. Furthermore, the catalyst preparation process is simple, and the cost of preparing a single N@C sheet-like carbon-based non-metallic electrode is only 0.6 yuan / g, significantly lower than the price of 1500 yuan / g for commercial IrO2 electrodes, and only 1 / 2500th the price of precious metal electrodes.

[0077] The pH values ​​of the H2SO4 and KOH solutions are the same as those of the commercial IrO2 anode electrode.

[0078] The basic parameters of the Hoffmann acid-base decoupling electrolytic hydrogen removal device are the same as those of the commercial anode IrO2 electrode.

[0079] The concentration gradient combinations for decoupled electrolysis of hydrogen using N@C sheet-like carbon-based non-metallic catalysts as the direct anode electrode in acid-base mixtures are shown in the table below.

[0080]

[0081] Figure 8 This is a diagram of the reaction apparatus for acid-base mixed decoupling electrocatalytic hydrogen evolution of the present invention. The left side is the anode, with a KOH solution as the anolyte, preferably 1.00M KOH; the right side is the cathode, with a H2SO4 electrolyte, preferably 0.50M H2SO4. A Nafion 117 membrane separates the anode and cathode chambers to prevent neutralization reactions and reduce the concentration gradient. A peristaltic circulation pump is installed on each side, with a liquid flow rate of 20 ml / min for the anode chamber on the left and 10 ml / min for the cathode chamber on the right.

[0082] In summary, the N@C sheet-like carbon-based nonmetallic catalyst prepared by high-temperature heat treatment in this invention has low energy consumption, mild conditions, simple operation, low equipment requirements, and is easy to implement. The prepared N@C carbon-based nonmetallic catalyst exhibits superior performance, with an average specific surface area of ​​189.593 m². 2 The N@C sheet-like carbon-based non-metallic catalyst of this invention has high reaction kinetics and good chemical stability. It possesses a high concentration of active components, and the surface structure can be adjusted by changing the raw material ratio. The invention utilizes a mixed acid-base solution with different concentration gradients for decoupled electrolytic hydrogen production, which exhibits superior performance compared to single-electrolyte acid or alkali solutions. The preferred anolyte is 1.00 M KOH, and the preferred catholyte is 0.50 M H₂SO₄. Results show that the OER performance of the N@C sheet-like carbon-based non-metallic electrode as the anode is superior to that of commercial IrO₂ as the anode. This catalyst is an economical and efficient alternative to the high-cost precious metals RuO₂ and IrO₂ used as anodes in water electrolysis for hydrogen production. Furthermore, it outperforms other non-metallic catalysts in terms of stability and OER performance.

[0083] The embodiments of the present invention have been described above. However, the present invention is not limited to the above embodiments. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. The application of a catalyst in acid-base decoupled electrolysis for hydrogen and / or oxygen production, characterized in that, The catalyst is prepared by a method including the following steps: mixing a carbon source with a phenolic resin and a nitrogen source, then pressing it into a compact, and then heat-treating it at high temperature in an ammonia atmosphere to prepare the catalyst. The high-temperature heat treatment temperature is 800 ~ 1000 °C; the high-temperature heat treatment is held at the same temperature for 100 ~ 150 min. The nitrogen source is selected from polydiallyldimethylammonium chloride; The carbon source is selected from a mixture of carbon nanotubes, conductive carbon black, graphite and activated carbon; The mass ratio of the carbon nanotubes, conductive carbon black, graphite, and activated carbon is 2~8:2~8:1~8:0.5~7; The amount of phenolic resin used is 10% to 30% of the total mass of the carbon source; The amount of nitrogen source used is 20% to 40% of the total mass of carbon source.

2. The application as described in claim 1, characterized in that, The mixing method is grinding.

3. The application as described in claim 1, characterized in that, The pressing method is cold pressing.

4. The application as described in claim 1, characterized in that, The diameter of the formed blank is 10~15 mm; the thickness of the formed blank is 1~3 mm.

5. The application as described in any one of claims 1-4, characterized in that, The flow rate of the ammonia (NH3) gas is 50 ~ 150 ml / min; And / or, the heating rate of the high-temperature heat treatment is 5~8 °C / min.

6. The application as described in any one of claims 1-4, characterized in that, The catalyst is in the form of flakes; The catalyst has a diameter of 10-15 mm and a thickness of 1-3 mm.

7. The application as described in any one of claims 1-4, characterized in that, In the catalyst, the amount of nitrogen doping is 1-5%; The catalyst has an average specific surface area of ​​180~200 m². 2 / g.

8. An electrolysis system, characterized in that, The electrolysis system includes an anode electrode plate, which is a catalyst prepared in any one of the applications described in claims 1-7.

9. The electrolysis system as described in claim 8, characterized in that, The electrolysis system further includes a cathode electrode plate, a bipolar membrane, an anode electrolyte and a cathode electrolyte, wherein the anode electrolyte and the cathode electrolyte are separated by the bipolar membrane.

10. The electrolysis system as described in claim 9, characterized in that, The electrolyte in the anode chamber is an alkaline solution; The concentration of the electrolyte used in the anode chamber is 0.50–1.00 M.

11. The electrolysis system as described in claim 9, characterized in that, The electrolyte in the cathode chamber is an acidic solution; The concentration of the electrolyte in the cathode chamber is 0.50–1.00 M.

12. The application of the electrolysis system according to any one of claims 8-11 in the electrolysis of water to produce hydrogen and / or oxygen.

13. The application as described in claim 12, characterized in that, The electrolysis system described herein is used in acid-base decoupled electrolysis for hydrogen and / or oxygen production.

Citation Information

Patent Citations

  • Metal-free carbon-based electrocatalyst, preparation method and applications thereof

    CN111001428A

  • Platinum-loaded nitrogen / sulfur co-doped porous carbon nanofiber material as well as preparation and application thereof

    CN113089136A

  • Method for preparing oxygen evolution electrocatalyst by using N-doped carbon-based material

    CN113430537A

  • Composite material and application thereof in device for producing hydrogen from electrolyzed water of acid-alkali electrolytic tank with assistance of urea oxidation

    CN108441885A

  • Electrolytic cell and application thereof in water electrolysis for hydrogen preparation

    CN110117797A